Basic principles of legal regulation in the field of human genomic information processing in the context of implementation of international legal norms to national legislation - Kovalenko, Mykola; Martynenko, Nataliia (Theory and Practice of Public Administration, 2022)
The article focuses on the analysis of human rights factors that are formed within the framework of international legal relations. The development of genomic research and expanding their application in domestic jurisprudence is a fairly new area of research in the field of public administration. On the basis of the synthesis of general scientific and specialized legal methods of research, the principles of regulation of relations on the processing of genomic information for human registration in Ukraine are formulated and substantiated, taking into account the threats to the dignity and rights of the human personality, namely: priority of life and health of citizens over interests of science and society in conducting molecular genetic examinations (research); confidentiality or protection of the genetic information of each citizen as part of personal data; equality of citizens regardless of genetic characteristics; guarantees of personality of person when using genomic technologies; observance of human and citizen’s rights and freedoms in the exercise of the rights and freedoms of others; guarantees of a citizen’s accessibility to their own genetic information; preventive actions of the state to protect citizens from the risks of loss, damage, distortion, misuse, unauthorized access to genomic information; exchange of genomic information with other countries and international organizations. In the context of implementation of international legal norms, the proposed principles are of particular importance, since they allow to maintain the balance of legal regulation and serve as a guide for law enforcement. The proposal for the application of a number of principles of processing of human genome information must be enshrined in the Law of Ukraine «On State Registration of Genomic Information», which will facilitate the formation of legal bases into the national system of law.